Game Edukasi Pencegahan Covid-19 Berbasis Android Untuk Usia 6-35 Tahun - Edora Edora; Mahrus Amin (Jurnal SIGMA, 2021)
Covid-19 pandemic, which is not over yet, has forced people to change their habits. The importance of health protocols can be used to reduce the spread of the Covid-19 virus. For that we need media or socialization about the importance of health protocols and efforts to prevent Covid-19 especially for age 6 – 35 years old. As for one of the alternative media that can be developed by looking at the rampant human activity in utilizing smartphones, is android game media. Covid-19 Prevention Educational Game was developed using the unity game engine. Application testing is carried out using the blackbox testing method while testing the feasibility of the system which is divided into two, that are efficiency and usability using the linkert scale. From this, it can be concluded that the application built has a feasibility level for sub-efficiency of 78% and for sub-usability of 83.5%. Keywords: Covid-19, Educational Games, Unity